Colonial Counterfactuals, the American Separationist Mindset, and Open-Minded Discourse on the Establishment Clause - Prud'homme, Joseph (Religions, 2023)
This work first develops the idea of an American Separationist Mindset—a deeply rooted and often unthinking supposition that the strict separation of church and state is the only defensible church-state arrangement under the Establishment Clause of the United States Constitution. Such a Mindset can make arguments for religious accommodationism difficult to be assessed openmindedly in contemporary constitutional discourse. The essay next surveys the potential of a counterfactual history of topics long thought settled to weaken prevailing views and treasured interpretations so to allow greater critical engagement with alternative assessments. The work in turn deploys a counterfactual reconstruction of Maryland’s colonial Anglican establishment. This account imagines the founding vision for Maryland’s establishment of Anglicanism developed by Rev. Thomas Bray as having been sustained. The cogency of this counterfactual can assist contemporary constitutional discourse by weakening the prejudicial potential of the American Separationist Mindset.